The Relationship Between Treatment Prescription and Standardized Assessment for Youth With Identified Trauma, Behavior Problems, or Substance Use - Verbist, A. Nathan; Winters, Andrew M.; Antle, Becky F.; Collins-Camargo, Crystal (Journal of emotional and behavioral disorders, 2022)
The use of standardized assessment in evidence-based practice (EBP) is critical in identifying empirically supported interventions (ESIs); however, the subject has received minimal attention in the literature. In a sample of child welfare involved youth, this study sought to determine whether there was a relationship between dimensions of trauma exposure, emotional/behavioral problems, and substance use problems, as identified in the Child and Adolescent Needs and Strengths (CANS) assessment conducted by behavioral health providers, and the type of prescribed ESI. Bivariate analysis of variance (ANOVA), chi-square tests, and multivariate binary logistic regression results suggest clinicians use assessment information to varying degrees when prescribing an ESI. Close to 90% of the sample was prescribed an ESI intended to address emotional or behavior concerns. Approximately one-fourth of the sample was prescribed a trauma-focused ESI, while substance use-focused ESIs were the least frequently prescribed. As the intensity of assessed trauma-related problems increased, so too did the odds of receiving an ESI intended to address trauma. To a lesser degree, as assessed emotional/behavior problems or substance use issues increased, the probability of being prescribed a related ESI also increased. Implications for practitioners, administrators, policymakers, educators, researchers, and other behavioral health stakeholders are discussed.